2017
DOI: 10.1021/acscatal.7b01436
|View full text |Cite
|
Sign up to set email alerts
|

Ring Opening of Biomass-Derived Cyclic Ethers to Dienes over Silica/Alumina

Abstract: We show that cyclic ethers, such 2-methyltetrahydrofuran (2-MTHF), can undergo dehydration to produce pentadienes over SiO2/Al2O3. The catalyst exhibited reversible deactivation due to coke deposition, with the yield to pentadienes decreasing from 68% to 52% at 623 K over 58 h time on stream. A reaction network for 2-MTHF dehydration was proposed on the basis of the results of space time studies. Pentadienes can be produced directly by a concerted hydride shift and dehydration of carbenium intermediates or ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(82 citation statements)
references
References 29 publications
4
76
2
Order By: Relevance
“…E a value decreased followed the order 2Ni/S‐1 (119.87 ± 3.73 kJ/mol) > 2Ni@S‐1 (117.54 ± 2.89 kJ/mol) > 2Ni0.5Pt/S‐1 (110.49 ± 3.58 kJ/mol) > 2Ni0.5Pt@S‐1 (100.41 ± 3.43 kJ/mol) which also support the exceptional activity of 2Ni0.5Pt@S‐1 for steam reforming of n ‐dodecane. The Mears and Weisz–Prater criteria equation were employed to exclude the external and internal mass transfer limitations …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…E a value decreased followed the order 2Ni/S‐1 (119.87 ± 3.73 kJ/mol) > 2Ni@S‐1 (117.54 ± 2.89 kJ/mol) > 2Ni0.5Pt/S‐1 (110.49 ± 3.58 kJ/mol) > 2Ni0.5Pt@S‐1 (100.41 ± 3.43 kJ/mol) which also support the exceptional activity of 2Ni0.5Pt@S‐1 for steam reforming of n ‐dodecane. The Mears and Weisz–Prater criteria equation were employed to exclude the external and internal mass transfer limitations …”
Section: Resultsmentioning
confidence: 99%
“…E a value decreased followed the order 2Ni/S-1 Weisz-Prater criteria equation were employed to exclude the external and internal mass transfer limitations. 74,75 Encapsulated bimetallic alloy catalyst exhibited not only exceptional activity and stability, but also high hydrogen selectivity. For 2Ni0.5Pt@S-1 and 2Ni@S-1, hydrogen selectivity was as high as 69.9 and 70.3%, respectively.…”
Section: Catalyst Characteristicsmentioning
confidence: 99%
“…Myrcene and Far are both found in nature, but can also be produced by pyrolysis of β‐pinene and microbial pathways from glucose, respectively. Although, there are new bio‐based pathways to synthesize butadiene and isoprene, myrcene and Far are made up of multiple isoprene units, which can provide different rheological properties. It was shown that bottlebrush polymers with densely packed, long side chains improve elastic properties .…”
Section: Introductionmentioning
confidence: 99%
“…In the first step, the deoxydehydration (DODH) of xylitol was conducted at 235 • C in the presence of formic acid to give 2,4-pentadien-1-ol, 1-formate (2E), with an optimized yield of 62.9%, followed by deoxygenation to obtain 1,3-pentadiene over a Pd/C catalyst at 100 • C. The total yield of 1,3-pentadiene reached 51.8%. Kumbhalkar et al [101] employed 2-methyltetrahydrofuran (2-MTHF) which can be easily obtained from biomass-derived intermediates (levulinic acid and furfural, etc. ), as the starting material to produce 1,3-pentadiene in a continuous system.…”
Section: Synthesis Of Isoprenementioning
confidence: 99%
“…The total yield of 1,3-pentadiene reached 51.8%. Kumbhalkar et al [101] employed 2-methyltetrahydrofuran (2-MTHF) which can be easily obtained from biomass-derived intermediates (levulinic acid and furfural, etc. ), as the starting material to produce 1,3-pentadiene in a continuous system.…”
Section: Synthesis Of Isoprenementioning
confidence: 99%